Analisis Keterampilan Dasar Mengajar Mahasiswa Pada Mata Kuliah Praktek Proses Pembelajaran Biologi - Maria Paulin Sari Dewi (Biota, 2017)
As a prospective teacher, students need to be trained in basic teaching skills before doing Field Experience Practice (PPL). Therefore, it is necessary to conduct research on the level of mastery of basic skills of teaching students. The purpose of this study is to know the basic skills of teaching students, the subjects of Biology Learning Process Practice, Biology Education Study Program, Teacher Training and Education Faculty, Widya Mandira Catholic University, Academic Year 2016/2017. This research is a quantitative descriptive research. The instrument used is the basic teaching skill assessment instrument. Data were collected by observation method and analyzed by descriptive quantitative. The results showed that the average ability to open the learning and attitude in the learning process is very good, with the value of each 3,625 and 3,675; Mastery of teaching materials and learning process is quite good with the value of each 3,475 and 3,575. While the evaluation aspect is quite good with the value of 3,5375 and the ability to close learning is good with a value of 3.4.